Smart tattoo: technology for monitoring blood glucose in the future. (24th January 2019) - Meetoo, Danny; Wong, Louise; Ochieng, Bertha
Abstract : New ways of measuring blood glucose bring hope of easing the burden of diabetes management for patients living with the conditions. The smart tattoo is an innovation that represents a nascent nanotechnology, which is designed to be implanted within the skin to provide continuous and reliable glucose detection for individuals diagnosed with diabetes. The potential benefits of the smart tattoo are compelling not only due to the potential of these nanodevices to prevent diabetic complications and decrease the related social costs, but also due to ease of use and relative user comfort. However, despite the advantages of the smart tattoo, it is important that health professionals, in embracing nanotechnology, understand the ethical implications of using these innovative devices.